EFFECTS OF ROOT PLANTS AND LITTER ON SOIL MACROPOROSITY, INFILTATION RATE AND EROSION - Hanggari Sittadewi (Badan Pengkajian dan Penerapan Teknologi (BPPT), 2021)
Plant roots and litter produced by tree that grow have an important role in the entry of rainwater into the soil (infiltration) as water storage in the future. The effects of plant roots and litter on increasing infiltration rate is due to increased soil macroporosity. The presence of roots that spread in various layers in the soil profile will further increase the organic matter content of the soil and loosen the soil thereby increasing soil macroporosity. In addition, dead roots will form empty spaces that can be filled by infiltration water, as well as active roots that have gaps between roots and soil that can be filled infiltration water. The high infiltration rate will reduce the amount of excessive runoff water so as to reduce the occurrence of erosion.